ILC2s Improve Glucose Metabolism Through the Control of Saturated Fatty Acid Absorption Within Visceral Fat - Okamura, Takuro; Hashimoto, Yoshitaka; Mori, Jun; Yamaguchi, Mihoko; Majima, Saori; Senmaru, Takafumi; Ushigome, Emi; Nakanishi, Naoko; Asano, Mai; Yamazaki, Masahiro; Takakuwa, Hiroshi; Satoh, Takashi; et al. (Frontiers in Immunology, 2021)
Background & Aims: Group 2 innate lymphoid cells (ILC2s) have been implicated in the regulation of metabolic homeostasis in mice. Methods: In this study, the role of ILC2s in white adipose tissue (WAT) was investigated using ST2, an IL-33 receptor that is expressed on ILC2s, knockout mice. Results: The deficiency of ST2 decreased ILC2s in WAT, whereas ex-ILC2, which acquired group 1 innate lymphoid cells (ILC1s)-like traits, was increased. This led to significant metabolic disorders such as visceral fat obesity, decreased browning in WAT, reduction of energy metabolism, and impaired glucose tolerance, compared to wild type (WT) mice. Those metabolic abnormalities of ST2-knockout (ST2KO) mice were not ameliorated by IL-33 administration, but impaired glucose tolerance and visceral fat obesity were significantly improved by transplantation of ILCs from the bone marrow of WT mice. The relative expression of Cd36 in WAT increased due to the deficiency of ST2, and the storage of saturated fatty acids in WAT of ST2KO mice was significantly higher than that of WT mice. Moreover, saturated fatty acids aggravated the chronic inflammation in adipocytes, promoted the differentiation of M1-like macrophages, and inhibited that of M2-like macrophages. Conclusions: Our results indicated that ILC2 regulates diet-induced obesity and chronic inflammation through the regulation of saturated fatty acid absorption in visceral adipose tissue.